IFN-γ reprograms cardiac microvascular endothelial cells to mediate doxorubicin transport and influences the sensitivity of mice to doxorubicin-induced cardiotoxicity - Haoyu Ji; Wenya Ma; Xu Liu; Hongyang Chen; Yining Liu; Zhongyu Ren; Daohong Yin; Ao Cai; Zizhen Zhang; Xin Wang; Wei Huang; Leping Shi; et al. (Experimental and Molecular Medicine)
Abstract Doxorubicin (DOX) is a first-line chemotherapy agent known for its cardiac toxicity. DOX-induced cardiotoxicity (DIC) severely limits the use for treating malignant tumors and is associated with a poor prognosis. The sensitivity to DIC varies among patients, but the precise mechanisms remain elusive. Here we constructed a mouse model of DIC using DOX to investigate potential mechanisms contributing to the differential susceptibility to DIC. Through surface-enhanced Raman spectroscopy and single-cell RNA sequencing, we explored the mechanisms underlying DIC phenotypic variations. In vitro and in vivo studies with small-molecule drugs were conducted. DIC-insensitive mice displayed preserved ejection fractions, lower DOX levels in cardiac tissues and higher levels in the serum. Single-cell RNA sequencing revealed differences of gene expression in cardiac endothelial cells between DIC-insensitive and DIC-sensitive groups. The expression of IFN-γ pathway-related genes was high in DIC-insensitive mice. IFN-γ administration decreased the DOX distribution in cardiac tissues, whereas PPAR-γ activation increased DIC susceptibility. IFN-γ stimulation upregulated P-glycoprotein expression, leading to increased DOX efflux and DIC insensitivity. Our model provides insights into the mechanisms of DIC sensitivity and potential preventive strategies.